Controle de Macrophomina phaseolina em soja por extrato de alecrim e análise dos mecanismos de defesa envolvidos - Lorenzetti, Eloísa (2017)
Several works using extracts obtained from medicinal plants have demonstrated direct and potential antimicrobial action to induce the accumulation of secondary metabolites, which are very important as plant defense mechanisms against pathogens. The objective of this work was to develop an alternative method using rosemary extract (Rosmarinus officinalis L.) at concentrations 0%, 1%, 2.5% and 5%, to verify the antimicrobial activity against Macrophomina phaseolina, control of charcoal rot in soybean stem and determine the activity of peroxidase, polyphenol oxidase, phenylalanine ammonia-lyase (PAL) and protein content on soybean plants. We performed in vitro assays in order to analyze mycelial growth of the fungus, fungus mass and number of micro-sclerotia, greenhouse tests to evaluate the area under the disease progress curve (AUDPC), and biochemical analyzes to verify a possible induction of resistance in the treated plants. For the determination of the defense enzymes, soybean plants were treated with the extracts and inoculated with M. phaseolina. Samples were collected at 0, 36, 72, 120, 168, 216 and 264 h after treatment. The rosemary extract reduced by 44% and 74% the fungal growth on solid and liquid media, respectively, while for the micro-sclerotia the reduction was of 61%. For the AUDPC in the first and in second assays, there were a reduction of 53% and 56% respectively in the disease. For the samples collected at the base of steam, peroxidase had the highest concentrations of the extract with two peaks of induction. The polyphenol oxidase activity increased from 36 to 120 hours after treatment with extract at 5%. PAL activity was induced only with 5% extract, with increases 83% and 130% higher in times 168 and 216 hours after treatment, respectively. For enzymes activities in root, peroxidase again showed two peaks for increase at 5% concentration, polyphenol oxidase was 426% higher at 216 hours after treatment and PAL showed an increase of 340% at 216 hours after treatment with 5% extract. These results indicate potential of rosemary extract in the control of charcoal rot in soybean and in the induction of plant defense enzymes in soybean.